الصحة التنظيمية وعلاقتها بالارتباط الوظيفي لدى العامل بالمؤسسة -دراسة ميدانية بالوكالة التجارية لاتصالات الجزائر بالمسيلة - بلوم, اسمهان; عيواز, نور الدين (جامعة الوادي - University of Eloued, 2018)
هدفت هذه الدراسة إلى التعرف على مدى أهمية توفر ثقافة الصحة التنظيمية في المنظمة والارتباط الوظيفي كسلوك لدى العامل، وما يضمنانه من فعالية العدالة والسلطة التلاؤمية، التمكين والاستغراق الوظيفي كأحد الآليات الكفيلة بتطوير المنظمة بما يتماشي ومتطلبات العصر . ولقد اسفرت هذه الدراسة؛ على أن الصحة التنظيمية تساهم في توفير معالم الكفاءة المهنية والفعالية التنظيمية والارتقاء بالروح المعنوية لدى الفئة العاملة، كما تساهم في تنمية القدرات والمهارات الفكرية والإبداعية لدى العمال وذلك من خلال مجهودات إدارة المنظمة والعمل على تحقيق الظروف الملائمة للعمل والسعي إلى تحقيق بيئة عملية تتميز بالإنسانية.The aim of this study is to identify the importance of the culture of the organizational health in the organizations and as well the job correlation as a behavior guaranteeing effective justice and adaptive power, empowerment and job obsession as one of the mechanisms to develop the organization. This study concluded that organizational health contributes in enhancing professional competencies; organizational effectiveness and in rising the employees morale, and as well contributes to the development of the intellectual and creative abilities and skills of the employees through the efforts of the Organization staff and the efforts to achieve the conditions conducive to work besides the pursuit for a humanitarian practical environment.
مقال
Keywords: الصحة التنظيمية، الارتباط الوظيفي، المؤسسة.; organizational health , job correlation, institution